Portrait of the Servant from Dobromil Based on the Cognominal Novel by Halyna Pahutiak (Linguostylistic Studies, 2019)
The portrait of a character, along with the descriptions of landscapes, interiors, monologues, and dialogues, is a part of the literary text structure, creating the artistic picture of the work. The issue of the language portrait is of great interest in modern linguistic and stylistic studies, and, mainly, due to the ambiguity of the term interpretations. We assume the language portrait of a character as a set of lexical and stylistic means involved by the author to describe the appearance, nonverbal characteristics, speech, character traits, thoughts dynamics, feelings, and experiences of the character. The purpose of the research is to analyze the lexical and stylistic means of creating a linguistic portrait of the main character from Halyna Pahutiak's novel The Servant from Dobromyl. The stylistic devices and expressive means used to describe appearance features are essential for the physical portrait of the character, the formulation of his value priorities – for the psychological portrait, and his social status – for the social portrait. All these aspects are organically combined in the novel by H.Pahutiak, in the image of the Servant – dhampir, a mythical creature in the human body. Lexical and linguistic-stylistic means play a significant role in the creation of the Servant's linguistic portrait: repetitions, contextual synonyms, antonymous pairs, stylistic figures of antonomasia, antitheses, direct citation and reinterpretation of the biblical aphorisms. The main character in the work appears under several names – Servant, the Borrowed, Sower, Sylvester, which transmit information about his role-function, help to identify his status in society. The choice of a name is not just a formal act but also an element of the social-linguistic portrait of the character. The physical portrait of the protagonist of the novel is presented briefly. The somatic features are predominantly the descriptions of only eyes, lips, hair. Westisms are most often represented by the general nominatheme of clothing. In the description of the non-verbal behavior, the emphasis is on the unusual touching smile of the Servant. Creating the psychological portrait, the author uses a number of lexical means that accentuate the features of character, temperament, mood, or worldview. In the structure of emotional and value-related expressions,  the nominations of oppositional rows dominate (a loyal servant – bad servants, the generosity of the soul – the generosity of the purse, forgiveness/mercy – revenge). Synonyms with positive and negative connotations reinforce the emotional and semantic significance of the values inherent in the concept of worldview, which the Servant pursues. The protagonist's speech is rich in aphorisms. Quotes from the Bible, which reflect the fundamentals of Christian ethics, and their interpretation are apprehended as the ideas of the protagonist's individual philosophy. In general, the linguistic portrait of the Servant from Dobromyl absorbs a whole set of the features, dispersed in the novel.
Keywords: character; language portrait; psychological portrait; description of appearance; lexical and stylistic means